1995
DOI: 10.1130/0091-7613(1995)023<0779:holmft>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

History of Laurentide meltwater flow to the Gulf of Mexico during the last deglaciation, as revealed by reworked calcareous nannofossils

Abstract: The history of meltwater flow from the Laurentide Ice Sheet to the Gulf of Mexico during the last deglaciation, which holds possible implications for the cause of the Younger Dryas cold episode, is not well understood. We propose a new chronology based on using the percentage of reworked calcareous nannofossils in Orca Basin sediments as a proxy for erosion. The period of greatest meltwater flow to the gulf was between 12.7 and 12.1 ka (during the Bølling warm interval), and flow remained high until the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 27 publications
(48 reference statements)
4
26
0
Order By: Relevance
“…All support the variable influence of LIS meltwater in the Gulf of Mexico during the last deglaciation (Flower et al, 2011). In addition to an isotopic signature from LIS meltwater, evidence from proxies of continental erosion (Brown and Kennett, 1998;Marchitto and Wei, 1995;Meckler et al, 2008) indicates that a large volume of freshwater runoff from the LIS was directed into the Gulf of Mexico during the last deglaciation, with a dynamic melting history and periods of high meltwater discharge (Brown and Kennett, 1998). Gulf of Mexico in the past also presents challenges.…”
Section: Materials and Analysesmentioning
confidence: 85%
“…All support the variable influence of LIS meltwater in the Gulf of Mexico during the last deglaciation (Flower et al, 2011). In addition to an isotopic signature from LIS meltwater, evidence from proxies of continental erosion (Brown and Kennett, 1998;Marchitto and Wei, 1995;Meckler et al, 2008) indicates that a large volume of freshwater runoff from the LIS was directed into the Gulf of Mexico during the last deglaciation, with a dynamic melting history and periods of high meltwater discharge (Brown and Kennett, 1998). Gulf of Mexico in the past also presents challenges.…”
Section: Materials and Analysesmentioning
confidence: 85%
“…It had been thought that flow returned to the Gulf of Mexico after blockage of eastern outlets about 9.9 ka BP. However, it now appears that Lake Agassiz discharged northward at that time into the Arctic Ocean via glacial Lake McConnell (Fisher and Smith, 1995), that this flow continued until re-establishment of eastward drainage about 9.5 ka BP, and that meltwaterflow never resumed down the Mississippi River (Marchitto and Wei, 1995).…”
Section: Molluscan Zones At 10 Ka Bpmentioning
confidence: 99%
“…17) (Flower and Kennett, 1990;Marchitto and Wei, 1995;Aharon, 2003). During this period, the Mississippi River discharge and the size and amount of sediment load was were significantly reduced.…”
Section: Discussionmentioning
confidence: 90%
“…17) from 11,000 to 10,000 cal yr B.P., was marked by at least four meltwater flood periods (Aharon, 2003). Increased meltwater flow to the Gulf of Mexico has been shown to have greatly enhanced the erosion of stored sediments in the Mississippi Alluvial Valley (Marchitto and Wei, 1995). It is suggested that these meltwater episodes caused erosion of the upstream channel.…”
Section: Discussionmentioning
confidence: 98%